PKM STRATEGI PENYUSUNAN DAN PENGAJUAN KEKAYAAN INTELEKTUAL - Titin Titin (STKIP Persada Khatulistiwa Sintang, 2019)
Intellectual Property for universities is very important, because it can strengthen accreditation, academic processes, community empowerment, and sources of information, as well as foster the pride of the college itself. To encourage increased intellectual property in tertiary institutions, active roles from various parties, namely lecturers and students are needed. During this time, from the results of research and community service produced by lecturers and students, the Biology Education Study Program which contains publications in the form of articles that are disseminated and published in scientific journals. Only a few are made as a result of Intellectual Property and their numbers are very few. For this reason, it is necessary to look for alternatives in the context of research downstreaming, and use research / community service for Intellectual Property to increase the intellectual property index of the Biology Education Study Program of FKIP Tanjungpura University. One alternative that can be done is through Community Service preparation of strategies and submissions of Intellectual Property. The method used is socialization and assistance. Study Strategies and mentoring for students of Biology Education Study Program FKIP Tanjungpura University. The activities carried out received positive responses from all participants who received benefits and some were interested in carrying out the proposed IP application independently.